Management of pancreatic head adenocarcinoma: From where to where? - Dolay, Kemal (World J Gastrointest Surg, 2019)
Pancreatic head adenocarcinoma (PHAC) is one of the most aggressive malignancies, and it has low long-term survival rates. Surgery is the only option for long-term survival. The difficulties associated with PHAC include higher frequencies of regional or distant lymph node metastases and vascular involvement, and positive resection margins in pancreatic and retroperitoneal tissues. Radical resections increase margin negativity and life expectancy; however, the extend of the surgery applied is controversial. Thus, western and eastern centers may use different approaches. Multiorgan, peripancreatic nerve plexus, and vascular resections have been discussed in relation to radical surgery for pancreatic cancer as have the roles of neoadjuvant and adjuvant therapy regimens. Determining the appropriate limits for surgery, standardizing definitions and surgical techniques according to guidelines, and centralizing pancreatic surgery within high-volume institutions to reduce mortality and morbidity rates are among the most important issues to consider. In this review, we evaluate the basic concepts underlying and the roles of radical surgery for PHAC, and lymphadenectomy, nerve plexus, retroperitoneal tissue, vascular, and multivisceral resections, total pancreatectomy, and liver metastases are discussed.